Validated UPLC-MS/MS Method for Determination of Futibatinib and Its Pharmacokinetics in Beagle Dogs - Heng Li; Hao-Zhe Ding; Yi-Lin Wang; Feng Zhang; Ya-Hao Song; Xiang-Jun Qiu (Journal of Chemistry)
Futibatinib, a highly selective, irreversible potent fibroblast growth factor receptor (FGFR) inhibitor, has been proved to be effective in clinical trials of intrahepatic cholangiocarcinoma (ICCA) patients. An ultra-high performance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) method to determine the concentration of futibatinib in beagle dog plasma was developed and validated for the study of pharmacokinetics. After the plasma protein was removed by acetonitrile precipitation, futibatinib was detected and derazantinib was used as the internal standard (IS). Futibatinib and IS were separated in an UPLC BEH C18 column (2.1 mm × 50 mm, 1.7 μm) with acetonitrile and 0.1% formic acid as the mobile phase, and the flow rate was 0.3 mL/min. Under the positive ion condition of an electrospray spray ion (ESI+) source, multireaction detection was used, and the ion pairs for futibatinib and IS were m/z 418.99 ⟶ 295.97 and 468.96 ⟶ 382.00, respectively. Futibatinib had a good linear relationship in the linear range of 0.5∼100 ng/mL; the lower limit of quantification (LLOQ) was 0.5 ng/mL. The RSDs of the intraday and interday precision were all less than 10.70%, and the RE value of accuracy was between −3.87% and 3.28%. The extraction recovery of futibatinib was more than 80%, and the matrix effect was around 100%, and futibatinib was found to be stable under four experimental conditions. The new optimized and validated UPLC-MS/MS method was an effective tool to determine the concentration of futibatinib in plasma and has been successfully applied to the pharmacokinetics of futibatinib in beagle dogs. This method would also be used to study drug-drug interaction (DDI).